(untitled) (Philadelphia, PA, 2002)
This 2-volume reference offers a practical approach to diseases of the muscle, neruo-muscular junction, and spinal cord. Volume I emphasizes the pathophysiology of neuromuscular disease and its assessment using electrophysiologic and radiologic tools. Volume II focuses on the application of electrophysiologic testing to the diagnosis and management of specific neuromuscular disorders. These books explore HIV, clinical trials, and neuromuscular disorders in critical care and the operating room. It Integrates all the guidance needed to diagnose and manage the full range of neuromuscular diseases.
Keywords: Neuromuscular diseases.,Neuromuscular diseases; Diagnosis.,Treatment